Kekuatan Pembuktian Akta Dibawah Tangan Dalam Hukum Acara Perdata - Nisa, Ayu Chairun (Jurnal Litigasi Amsir, 2023)
This study aims to find out and analyze the strength of proof that an underhanded deed can provide legal certainty and to find out and analyze the weaknesses of proving an underhanded deed as evidence. This research uses normative-empirical research. The study results show the strength of proof of an underhanded deed to provide legal certainty if it fulfils the requirements and value of the underhanded deed, where the evidentiary requirements contain events that form the basis of a right or engagement affixed to the signature and made by the parties. Parties without the help of officials. Whereas in terms of the proof value of an underhanded deed, if from the echtheidsprosedure it cannot be proven the correctness of the signature on the underhanded deed, it means that the person concerned is deemed correct in dismissing it and the underhanded deed is aborted as evidence that has value. Conversely, if the signature on the private deed can be verified from the echinoids procedure but is still denied by the person concerned, it is a fact that the judge has found the truth of the statement above the private deed by itself also becomes sufficient evidence for the judge to consider. And the weakness of proving the deed under the hand is only limited to the formal and material sense, not the sense of birth. Because of this, what appears to be an underhand deed is not binding as evidence and becomes a real weakness in the trial, so in itself, it can become a basis for refusing to fulfil the contents of the agreement even if the statement and the contents of the agreement are recognized and justified.